Modeling and Simulation: Machining of Mild Steel Using Indigenously Developed Abrasive Flow Machine. (2016) - Seifu, Yared; Kumar, S. Santhosh; Hiremath, Somashekhar S.
Abstract: Abrasive Flow Machining (AFM) is an advanced nonconventional finishing process, in which viscoelastic polymer carrier medium mixed with suitable abrasive particle is forced through the workpiece having intricate profile/cavities for which high quality surface finish is prime significance. So AFM process is used for finishing, deburring, edge rounding and general improvement of surface quality of workpiece with complex geometries. In the present study modeling of abrasive flow machining including force modeling and material removal rate is presented. During the simulation computational fluid dynamic (CFD) analysis has been carried out while modelling convergent - divergent nozzle made of mild steel using ANSYS 15.0 software. The paper containing CFD simulation results of axial stress, radial stress, depth of indentation and material removal rate.